WITHIN THE FRAMEWORK OF GEOPOLITICAL CONDITIONS OF WORLD WAR I. IMPORTANCE OF THE CALIPHATE MOVEMENT FOR TURKEY AND INDIA - Ferhat Çağrı Aras; Yucel Bulut (İmgelem)
India shares excellent historical, cultural, and diplomatic contacts with the Ottomans. India’s connections with Ottoman Empire could be traced at least from the Ottoman capture of Istanbul in 1453. The Ottoman Sultans functioned as Caliph for nearly 80 million Mohammedans in India during the 19th century, revered for their control over holy places such as Jerusalem, Mecca, and Medina. The Mohammedan society within India heavily sympathized with Turkiye’s cause, including support from all religious and political classes. India was the only foreign country in the world that sent a medical mission to Turkiye during the Balkan Wars (1912-13). While Indian freedom fighters significantly understood the imperial and colonial policies of the West, to which Turkiye also found itself strangled from all sides during the late and initial phases of the 19th and 20th centuries.Sharif Hussein’s family played a crucial role in igniting the Arab revolt against the Ottoman Empire. But he could not evoke Caliphate to attain support from Mohammedan society in the post-war era due to the fear among the Islamic community of being the puppet of the West. Moreover, the Young Turk Movement and German Kaiser (protectorate) could not supersede the supra-national identity of Islam. Still, the rise of Nationalism under the Western protectorates heavily impacted the Ottoman control of Gulf/West Asia. The First World War and subsequent agreements dismantled the Ottomans’ regional authority. The Subsequent treatment of Ottomans under the Treaty of Sevres ignited the Indian response supporting the Turkish cause. This paper seeks to outline India- Turkiye relations during the Khilafat movement 1919-1924 and possible reasons for the help of the Khilafat movement.